PENGARUH KUALIFIKASI PENDIDIKAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI PEGAWAI NEGERI SIPIL BIDANG PERBENDAHARAAN DAN KAS DAERAH KOTA PROBOLINGGO - Suharno Suharno; Bambang Winarto (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study aims to determine the effect of educational qualifications and compensation on employee performance through the motivation of civil servants in the regional treasury and treasury sector in Probolinggo City. The type of research used is quantitative research. The data collection method is by distributing questionnaires offline by asking 5 questions per variable. A sample of 35 Civil Servants in the Regional Treasury and Cash Office of the City of Probolinggo uses the simple proportional sampling method. This type of research is a method of descriptive analysis and data verification using the SmartPLS 3.0 application. The results show that educational qualifications have no significant effect on motivation. Variable educational qualifications have no significant effect on performance. The pressure has no significant effect on motivation. The compensation has a significant effect on performance. The motivation has no significant effect on performance in Civil Servants in the Treasury and Regional Cash Office of the City of Probolinggo.